Konsep Nafkah dalam Tafsîr Asy-Sya’rawî: Studi Tafsir Tematik Tokoh dan Relevansinya Terhadap Kehidupan Keluarga Kontemporer - Sadad Robith Adani; Ibnu NB At-Thoriq; Akhmadiyah Saputra (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines the concept of nafāqah (living) in the interpretation of Sheikh Muhammad Mutawalli Asy-Sya’rawi through the thematic interpretation approach of figures (tafsīr maudhu‘ī al-shakhṣī). This study focuses on the verses of the Qur’an related to financial responsibility in the family, especially QS. An-Nisa’ : ​​34 and QS. At-Talaq : 6-7. Using qualitative library research methods, data were collected from the book Tafsir Khawatir Ash-Sya’rawi Haul Al-Qur’an Al-Karim and analyzed through thematic content analysis. The results of the study show that Asy-Sya’rawi interprets living not only as a legal obligation but as a comprehensive responsibility that includes social, moral, and spiritual dimensions. The concept of living is closely related to the concept of qiwāmah, which emphasizes the principles of justice, protection, and proportionality according to the husband’s financial capabilities. Furthermore, Asy-Sya'rawi's interpretation demonstrates flexibility and contextual relevance, making it applicable to contemporary family challenges, including economic inequality and post-divorce responsibilities. This research contributes to enriching contemporary Qur'anic studies by presenting a contextual and responsive interpretation of livelihood to social issues.